A filosofia da educação de Luís Antônio Verney: entre o iluminismo e uma nova escolástica - Buonadio Neto, Vicente (2013)
Monographic study, historical interpretation in the area of philosophy of education. In True Method of Studying, Luis Antonio Verney openly criticizes the education provided by the Jesuits, blaming them for all cultural and educational backwardness of the Kingdom. Grounded in modern philosophy, Verney, proposes a reform at all levels of educational Portugal - primary, secondary and higher education - formulating a new ideology of education for the state. Based on empiricism, which started from the observation and experience, contrasted to the formal logic of the deductive method of the scholastics, foundation of Ratio Studiorum of the Jesuits. His criticisms and proposals influenced the creation of the first secular educational system in Portugal, after the expulsion of the Jesuits in the reforms of Pombal. While that seems to have disrupted with the scholastic model by proposing empiricism, his enlightenment was conservative, not revolutionary, Catholic, because he always defended the maintenance of (the) faith , fidelity to the Church, conciliation between faith and reason , which are the foundations of scholasticism. In this work, the following questions are raised: What were the main characteristics of the Enlightenment of Portuguese pedagogy? Did Verney disrupt scholasticism? Or just added some ideas of modern philosophy, maintaining the essence of that current of thought? This work seeks to understand how the creation of Portuguese public education occurred, and thus better understand, too, the Brazilian education. Bibliographical monography based upon the historical-critical methodology. We conclude that Verney disrupted scholasticism partially, by proposing a new method based on empiricism of Locke and blaming the Jesuit educational model for the delay of the kingdom, but at the same time kept as Portuguese priest the ideology of the Catholic faith, and, because of that he created a new Portuguese scholastic. He brought major contributions to the educational reform in the kingdom such as the appreciation of the Portuguese to the Latin, the secularization of the educational system, the education of women, literacy for all subjects, the creation of a new academic education based on the appreciation of the experience, among others.